Understanding wood a craftsman's guide to wood technology - Hoadley, R. Bruce 1933-
"Understanding Wood is updated to include new information on composite materials, adhesives, and finishes developed in the past 20 years. R. Bruce Hoadley explores the nature of wood and its properties, the basics of wood technology, and the woodworker's raw materials. You'll learn the best ways to cut, season, machine, join, bend, fasten, and finish wood, and explore the crucial interaction of wood and moisture. You'll also find the latest on wood products and where to buy them."--BOOK JACKET